Are Tenure Track Professors Better Teachers? - Figlio, David N.; Schapiro, Morton O.; Soter, Kevin B. (The Review of Economics and Statistics, 2015)
This study makes use of detailed student-level data from eight cohorts of first-year students at Northwestern University to investigate the relative effects of tenure track/tenured versus contingent faculty on student learning. We focus on classes taken during a student’s first term at Northwestern and employ an identification strategy in which we control for both student-level fixed effects and next-class-taken fixed effects to measure the degree to which contingent faculty contribute more or less to lasting student learning than do other faculty. We find consistent evidence that students learn relatively more from contingent faculty in their firstterm courses. This result is driven by the fact that the bottom quarter of tenure track/tenured faculty (as indicted by our measure of teaching effectiveness) has lower “value added” than their contingent counterparts. Differences between contingent and tenure track/tenured faculty are present across a wide variety of subject areas and are particularly pronounced for Northwestern’s averages and less-qualified students.